Is there a giant Kelvin-Helmholtz instability in the sloshing cold front of the Perseus cluster? - Walker, S.; Hlavacek-Larrondo, J.; Gendron-Marsolais, M.; Fabian, A.; Intema, Hubertus; Sanders, J.; Bamford, J.; van Weeren, R. (Oxford University Press, 2017)
Deep observations of nearby galaxy clusters with Chandra have revealed concave ‘bay’ structures in a number of systems (Perseus, Centaurus and Abell 1795), which have similar X-ray and radio properties. These bays have all the properties of cold fronts, where the temperature rises and density falls sharply, but are concave rather than convex. By comparing to simulations of gas sloshing, we find that the bay in the Perseus cluster bears a striking resemblance in its size, location and thermal structure, to a giant (≈50 kpc) roll resulting from Kelvin–Helmholtz instabilities. If true, the morphology of this structure can be compared to simulations to put constraints on the initial average ratio of the thermal and magnetic pressure, β = pth/pB, throughout the overall cluster before the sloshing occurs, for which we find β = 200 to best match the observations. Simulations with a stronger magnetic field (β = 100) are disfavoured, as in these the large Kelvin–Helmholtz rolls do not form, while in simulations with a lower magnetic field (β = 500), the level of instabilities is much larger than is observed. We find that the bay structures in Centaurus and Abell 1795 may also be explained by such features of gas sloshing.